Microfinance, commercialisation and ethics - Reinhard H. Schmidt (Johann Wolfgang Goethe-Universität Frankfurt am Main, Fachbereich Wirtschaftswissenschaften, 2008)
This paper discusses the so-called commercial approach to microfinance under economic and ethical aspects. It first shows how microfinance has developed from a purely welfare-oriented activity to a commercially relevant line of banking business. The background of this stunning success is the almost universal adoption of the so-called commercial approach to microfinance in the course of the last decade. As the author argues, this commercial approach is the only sound approach to adopt if one wanted microfinance to have any social and developmental impact, and therefore the wide-spread moralistic criticism of the commercial approach, which has again and again been expressed in the 1990s, is ill-placed from an economic and an ethical perspective. However, some recent events in microfinance raise doubts as to whether the commercial approach has not, in a number of cases, gone too far. The evident example for such a development is the Mexican microfinance institution Compartamos, which recently undertook a financially extremely successful IPO. As it seems, some microfinance institutions have by now become so radically commercial that all of those social and development considerations, which have traditionally motivated work in the field of microfinance, seem to have lost their importance. Thus there is a conflict between commercial and developmental aspirations. However, this conflict is not inevitable. The paper concludes by showing that, and how, a microfinance institution can try to combine using the strengths of the capital market and at the same time maintaining its developmental focus and importance.
Keywords: A13; D63; F35; O16; 330; Development Finance; Microfinance; Commercialisation; IPO; Business Ethics; Mikrofinanzierung; Entwicklungsfinanzierung; Kommerzialisierung; Bankgeschäft; Unternehmensethik; Sozialethik; Welt